The The Impact of Features, Usability, and Perceived Benefits of Digital Financial Applications on Satisfaction and Loyalty of Generation Z University Students - Rieka Damayanti; Irawati Irawati (Indonesian Journal on Computing (Indo-JC), 2026)
This study compares three personal finance apps—Money Pocket, Catatan Keuangan, and Money Lover—used by Indonesian Generation Z students. An online purposive survey yielded 88 valid responses (Money Pocket n = 28; Catatan Keuangan n = 42; Money Lover n = 18). Reliability was acceptable (Cronbach’s α = 0.87–0.94). Mean scores (1–5) ranged from 3.90 to 4.20. One-way ANOVA identified a significant difference only in feature completeness (F = 4.12, p = 0.020); Tukey post-hoc tests showed Money Pocket > Catatan Keuangan (mean diff. = 0.33, p = 0.018). No significant inter-app differences were found for ease of use, perceived usefulness, satisfaction, or continuance usage intention. Overall satisfaction (3.96–4.12) and continuance usage intention (3.92–4.09) indicate moderate to high user approval. Developers should prioritize feature integration—bank synchronization, automated budgeting, bill reminders, and spending analytics—to enhance completeness and retention among student users.